ENHANCING ENDURANCE PERFORMANCE LEVEL OF YOUNG ELITE SOCCER PLAYERS USING AGILITY EXERCISES WITH THE BALL - Abdallah Mohammed Tayawi; Adnan Mohammed Shnawa (Proximus Journal Publishing, 2024)
The aim of the research was to investigate the effect of agility with ball exercises on the endurance performance of young elite football players
Keywords: Agility; Football; Elite Players